A Behavioral Index for Assessing Bison Stress Level during Handling and Demographic Predictors of Stress Response. Issue 1 (2nd January 2022) - Caven, Andrew J.; Leung, Katie G.; Vinton, Clara; Krohn, Brice; Wiese, Joshua D.; Salter, Jacob; Ranglack, Dustin H.
ABSTRACT: There are an estimated half-a-million Plains Bison ( Bison bison ) present in North America in commercial and conservation herds. Most bison are rounded up and "worked" annually for parasite control, veterinarian attention, and processing, making it important to understand the impacts of these operations. Research indicates bison generally experience higher levels of stress than cattle during similar handling processes. However, most methods for assessing stress-level during working are invasive, increase handling time, and paradoxically increase stress levels. We designed a behavioral index to assess bison stress level during handling and used it to evaluate various predictors of stress response in a semi-wild bison herd. We examined how sex, age, herd of origin, previous experience, calf rearing, and body condition influenced bison stress response during working operations from 2015 to 2017. Our results indicate that stress level decreased with age and previous experience being worked through a particular facility. Additionally, herd of origin influenced stress level, indicating that stress response may have a genetic or epigenetic component. Our study provides an easily applicable tool for monitoring bison stress levels.